FROM INHERITED RECIPES TO IMPROVISATIONAL SELF-AUTHORSHIP: FOOD, DIASPORA, AND GENDER IN DIANA ABU-JABER’S MEMOIRS - Mochammad Arif Fadilah; Hasnul Insani Djohar (PARADIGM: Journal of Language and Literary Studies, 2025)
This paper examines how Diana Abu-Jaber’s food memoirs, The Language of Baklava (2005) and Life Without a Recipe (2016), use food to negotiate questions of diasporic identity, gender, cultural inheritance, and self-authorship. Rather than treating food as a stable symbol of ethnic nostalgia, the study argues that Abu-Jaber presents meals, recipes, kitchens, and bodily responses as contested sites where belonging is remembered, fractured, revised, and remade. Using qualitative textual analysis informed by food studies, postcolonial and diaspora studies, and intersectional feminism, the article analyzes key culinary episodes, including the failed lamb slaughter, Bud’s Jordanian cooking, Grace’s baking, Diana’s nausea and reliance on lebeneh, the magloubeh scene, and the embedded recipes that interrupt the memoirs’ narrative structure. The findings show that food functions simultaneously as a sign of diasporic fracture, a Third Space of minority home-making, a gendered field of domestic power, a bodily site of refusal, and a formal strategy that disrupts linear autobiography. The comparison between the two memoirs reveals a movement from inherited culinary and cultural “recipes” toward improvisational self-authorship. By foregrounding food as memory, conflict, form, and agency, this paper contributes to Arab-American literary studies, food studies, and women’s life writing by showing that belonging in Abu-Jaber’s memoirs is not passively inherited but actively prepared, adjusted, and remade.